EVALUASI KERAGAMAN DAN STABILITAS KARAKTER PERTUMBUHAN DAN PRODUKSI 12 GALUR CALON VARIETAS JAGUNG HIBRIDA - Nurhana, Nanik; Kusmiyati, Florentina; Anwar, Syaiful (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
Corn is the number two stable crop in the world with increasing demand in line with population growth. The use of superior hybrid corn varieties is one of the solution in meeting the needs of corn throught plant breeding activities. The experimental design used was a monofactor randomized block design (RAK), with the object is 12 prosprective line of hybrid corn varieties from PT Tunas Widji Inti Nayottama (RD 422, RD 471, RD 491, RD 496, RD 551, RD 519, RD 523, RD 536, RD 586, RD 591, RD 602, RD 60), and control varieties is Bisi-18 and P31. The parameters observed included number of plants grown, high of plant, high of ear, lenght of ear, diameter of ear, weight of ear, weight of cob, number of seed rows pear earm number of seed per row, weight of 100 seeds, yield, seed moisture content, physiological maturity, and potential harvest. Variance analysis data and continued with the independent T test. The result showed that 7 corn lines which have the desired properties are RD 422, RD 471, RD 551, RD 519, and RD 603. The level of stability according to the coefficient of diversity, all of the test lines had low stability (uniform), except for RD 491 on the character of anxious weight (29.23%) and RD 602 on the character of the number of seeds per row (39.36%).